Silla 151C O Tuñipán - Blanco, Ricardo (2009)
Comentarios sobre la silla diseñada en 1956 para la firma Knoll Internacional.
Keywords: SAARINEN, EERO; ARQUITECTURA; DISEÑO INDUSTRIAL; MOBILIARIO; SILLAS; MOVIMIENTO MODERNO; HISTORIA